RITUAL PRACTICES OF THE MEETEIS - Devi, Waikhom Renuka (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The paper tries to give a brief analysis the critical, calendrical and cyclical rituals practice by the Meetei. Here the performance of the rituals has discussed who perform the rituals in the Meetei society and what the ingredients required for the performance of the rituals by taking some representative rituals for further elaboration. These rituals have been handed down from generations. Many of them are still practice today. The rituals like the rites which are performed during draught or birth or death of an individual are still practice forms of rituals among the Meeteis. All these rituals have their cultural significance and importance to the society and individuals in the society and they demonstrate the general belief system and practice system among the Meeteis.